2011
DOI: 10.1089/jmf.2010.0262
|View full text |Cite
|
Sign up to set email alerts
|

Volatile Compounds and Bioactivity ofEremurus spectabilis(Ciris), a Turkish Wild Edible Vegetable

Abstract: Eremurus spectabilis grows in the spring as a wild vegetable and for many years has been used both as a food or food additive and for therapeutic purposes. This study investigated the total phenolic content and the antimicrobial, antioxidant, and antiradical activities of methanol, ethanol, and aqueous extracts of E. spectabilis (obtained from the Antalya region of Turkey). In addition, volatile compounds of E. spectabilis were characterized by using gas chromatography/mass spectrometry. Major components of E.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 30 publications
2
24
1
Order By: Relevance
“…It is registered that E. spectabilis leaves are used traditionally in gastrointestinal disorders 12 . The results of our work are also supportive of this gastroprotective effect.…”
Section: ■ Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is registered that E. spectabilis leaves are used traditionally in gastrointestinal disorders 12 . The results of our work are also supportive of this gastroprotective effect.…”
Section: ■ Discussionmentioning
confidence: 99%
“…In addition to these, E. spectabilis has also antibacterial and antioxidant activities 10,11 . Carvone, carvacrol, pentane, (E)-caryophyllene, valencene were found to be as main constituents of the essential oil of E. spectabilis 12 . It is reported that inosine, methyl linolenate, chrysophanol, isoorientin, β-sitosterol and sucrose were also isolated from E. spectabilis 13 .…”
Section: ■ Introductionmentioning
confidence: 95%
“…Extracts of all three drugs (Eremurus spp, E. persicus and E. spectabilis) were prepared and their biological properties evaluated. First, extractions were performed using water and a water/methanol mixture, according to the literature (Karaman et al, 2011). In both cases, the formation of highly viscous solutions was observed, probably due to the presence of glucomannan, a water-soluble polysaccharide (Smirnova et al, 2001).…”
Section: Resultsmentioning
confidence: 99%
“…Both species have been traditionally used in Kurdish ethnomedicine to cure diseases having a common pathophysiological factor related to inflammation. It has been reported that the aerial parts of the plants, along with the rhizome and root nodules are eaten by native people for treating inflamed eyes, diabetes and eczema (Karaman et al, 2011;Yesil and Akalin, 2009), while their boiled roots are described to be efficacious in relieving rheumatism, gastrointestinal disorders (Ozturk and Olcucu, 2011), scabies (Karaman and Kocabas, 2001) and inflammatory skin conditions (Mamedov and Gardner, 2004) (Table 1).…”
Section: Introductionmentioning
confidence: 99%
“…Wang and Yang, 2007). The genus Eremurus is used in traditional folk medicine for the treatment and prevention of liver and stomach disorders, hemorrhoids and diabetes, and also for reducing dysuria and hypertension in many countries in central and western Asia (Karaman et al, 2011;Tosun et al, 2012;Xiao et al, 2012). Previous phytochemical investigations of the genus Eremurus revealed the presence of anthraquinones, naphthalene derivatives and polysaccharides (Asgarpanah et al, 2011;Berdikeev et al, 1982;Igamberdyeva et al, 1976;Li et al, 2000;Rakhimov and Yuldasheva, 1996;Yuldasheva and Rakhimov, 1996).…”
Section: Introductionmentioning
confidence: 99%